Kryteria i sposoby oceny pracy w mechanizmach regulacji płac - Jarmołowicz, Wacław (Wydział Prawa i Administracji UAM, 1986)
The basic question on which the author atempts to provide an answer are: what exactly is the subject of the work evaluation, what are its essential criteria end means, and particularly — what is the use of these evaluations in the centralized and decentralized types of the wage regulation mechanisms. As distinct from the traditional approach to the problems of work evaluation (accounting mostly for its „technical and account" aspect) the author attempts at discussing methods and tools of the evaluation from the viewpoint of the system of functioning of the national economy. Particularly, it is proved that the criteria, methods and tools of work evaluation are the essential element of mechanisms of wage regulation as the grounds for the decisionmaking on the level, relations and structure of wages. Reconstructing thus and analysing those mechanisms and the role played in them by the methods and tools of evaluating and regulating work, both conditioning of the system and certain effectiveness effects are indicated on the example of the Polish economy. First of all, the basic contradictions and limitations in accounting for work effectiveness as the basis for the decisionmaking in wages in the central regulation mechanism are presented. These are mainly resulted by reducing the notion of effectiveness to the evaluation of and measurements of work expenditures, particularly of individual labor. The necessity of departing from that „expenditure" handling of work evaluation related to shifting the stress in the evaluation to its results, including the collective results, and the consequent new approach to the criteria and means of evaluation, are in the author's opinion, the prerequisites to more rational and answering needs of the reform, wage policy.
The criteria and means of work evaluation in the wage regulation